Moderation of Profitability on Environmental, Social, Governance on Company Value in the Coal Mining Sector - Agnesti Indul; Gaguk Apriyanto; Parawiyati Parawiyati (Universitas KH. Abdul Chalim Mojokerto, 2026)
The key factor that investors need to consider before investing their capital is the assessment of the company's value. The purpose of this study is to analyze the moderating role of profitability on the influence of environmental, social, governance (ESG) on firm value. The analysis in the research uses quantitative analysis and the type of data is explanatory research with time series and cross section data from 2019-2023 using the moderated regression method with SPSS software. The research results state that there is a positive and significant effect of environmental, social, governance (ESG) on firm value, and the results of the profitability moderation analysis state that profitability has a significant effect on the effect of environmental, social, governance (ESG) on firm value, but has a negative moderation direction. These empirical results indicate that although ESG generally has a positive impact on firm value through increased stakeholder trust and social legitimacy, the presence of profitability as a moderating variable can weaken this effect. The implication of this finding is that coal mining companies need to increase ESG practices as it is proven to increase firm value by building market trust and good reputation. However, although profitability (ROA) strengthens the relationship between ESG and firm value, high profitability can reduce the focus on ESG. Therefore, companies need to maintain stability between profitability and ESG commitment, strengthen disclosure transparency, and utilize ESG practices as a competitive advantage to maintain social legitimacy and competitiveness in the global market.